Positive impact of IGF-1-coupled nanoparticles on the differentiation potential of human chondrocytes cultured on collagen scaffolds - Pasold J (Dove Medical Press, 2015)
Juliane Pasold,1 Kathleen Zander,1 Benjamin Heskamp,1 Cordula Grüttner,2 Frank Lüthen,3 Thomas Tischer,1 Anika Jonitz-Heincke,1 Rainer Bader1 1Department of Orthopaedics, Biomechanics and Implant Technology Laboratory, University Medicine Rostock, Rostock, Germany; 2Micromod Particletechnology GmbH, Rostock, Germany; 3Institute of Cell Biology, University Medicine Rostock, Rostock, Germany Purpose: In the present study, silica nanoparticles (sNP) coupled with insulin-like growth factor 1 (IGF-1) were loaded on a collagen-based scaffold intended for cartilage repair, and the influence on the viability, proliferation, and differentiation potential of human primary articular chondrocytes was examined. Methods: Human chondrocytes were isolated from the hyaline cartilage of patients (n=4, female, mean age: 73±5.1 years) undergoing primary total knee joint replacement. Cells were dedifferentiated and then cultivated on a bioresorbable collagen matrix supplemented with fluorescent sNP coupled with IGF-1 (sNP–IGF-1). After 3, 7, and 14 days of cultivation, cell viability and integrity into the collagen scaffold as well as metabolic cell activity and synthesis rate of matrix proteins (collagen type I and II) were analyzed. Results: The number of vital cells increased over 14 days of cultivation, and the cells were able to infiltrate the collagen matrix (up to 120 µm by day 7). Chondrocytes cultured on the collagen scaffold supplemented with sNP–IGF-1 showed an increase in metabolic activity (5.98-fold), and reduced collagen type I (1.58-fold), but significantly increased collagen type II expression levels (1.53-fold; P=0.02) after 7 days of cultivation compared to 3 days. In contrast, chondrocytes grown in a monolayer on plastic supplemented with sNP-IGF-1 had significantly lower metabolic activity (1.32-fold; P=0.007), a consistent amount of collagen type I, and significantly reduced collagen type II protein expression (1.86-fold; P=0.001) after 7 days compared to 3 days. Conclusion: Collagen-based scaffolds enriched with growth factors, such as IGF-1 coupled to nanoparticles, represent an improved therapeutic intervention for the targeted and controlled treatment of articular cartilage lesions. Keywords: chondrogenic differentiation, silica nanoparticles, growth factor, 3D-matrix, cartilage repair